Building Character Education through Scout Activity - Achmad Jazuli; Ahmad Syafii (STKIP Al Hikmah Surabaya, 2021)
Character education is mostly discussed around academic researchers, they are discussing deeply about how the impact of education to build a character which have many effects so it would be reinforcement for students’ character nowadays. Therefore, many researchers try to increase the ability of student potential good character. Several things that being a way to support the education as a place for developing character education in national student which hope that would better before the education have. Scout is considered able to change students’ character from the individuality student to be more active and creative, discipline, independent and so on. This paper is hoping that scout activity is going to be a builder for character education in order that can be proved by researcher and other.